Immunity index - Burke, Sue, 1955- (Tor, 2021)
"In a US facing growing food shortages, stark inequality, and a growing fascist government, three perfectly normal young women are about to find out that they share a great deal in common. Their creator, the gifted geneticist Peng, made them that way--before such things were outlawed. Rumors of a virus make their way through an unprotected population on the verge of rebellion, only to have it turn deadly. As the women fight to stay alive and help, Peng races to find a cure--and the cover up behind the virus"--